2012
DOI: 10.1603/me11225
|View full text |Cite
|
Sign up to set email alerts
|

The Potential Distribution ofPhlebotomus papatasi(Diptera: Psychodidae) in Libya Based on Ecological Niche Model

Abstract: The increased cases of cutaneous leishmaniasis vectored by Phlebotomus papatasi (Scopoli) in Libya have driven considerable effort to develop a predictive model for the potential geographical distribution of this disease. We collected adult P. papatasi from 17 sites in Musrata and Yefern regions of Libya using four different attraction traps. Our trap results and literature records describing the distribution of P. papatasi were incorporated into a MaxEnt algorithm prediction model that used 22 environmental v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
24
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 20 publications
8
24
0
Order By: Relevance
“…The seasonality in our data was also confirmed by the significance of trend and sinusoidal wave term as well as precipitation and temperature in our final model. These findings are similar to other studies indicating a positive association between precipitation, temperature and leishmaniasis [39,53].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The seasonality in our data was also confirmed by the significance of trend and sinusoidal wave term as well as precipitation and temperature in our final model. These findings are similar to other studies indicating a positive association between precipitation, temperature and leishmaniasis [39,53].…”
Section: Discussionsupporting
confidence: 92%
“…Precipitation and temperature provides significant contribution in predicting the suitable condition for leishmaniasis with average precipitation in April contributing the greatest. This is similar to studies that found precipitation to contribute significantly to the predictive probability of the presence of leishmaniasis [19,39] and sandflies [53].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…So, our findings can be used in future ecological studies on the potential of presence for this main vector of zoonotic cutaneous leishmaniasis in Iran and other parts of its' geographical distribution around the world. Study on potential distribution of P. papatasi in Libya using MaxEnt model showed precipitation had the most influence, while temperature and elevation had less weight in the model (Abdel-Dayem et al, 2012). Since this sand fly is peridomestic species and opportunistic feeder but prefers to feed on humans and rodents (Yaghoobi-Ershadiet al,1995), it can easily breed around the human dwellings.…”
Section: Discussionmentioning
confidence: 99%